BEoF: An Approach to Protecting Encrypted Messages Within Digital Images - Anto; Muhammad Amrizal Arripai; Muhammad Fadlan (AI Society & STMIK Indonesia, 2024)
This research develops and implements a combined technique of steganography and cryptography to enhance the security of messages within digital media. This research introduces BeoF, a novel technique combining End of File (EOF) steganography with Beaufort Cipher cryptography to secure text messages within digital images. The study demonstrates that EOF effectively hides text messages without significantly degrading image quality. Beaufort Cipher adds a security layer by encrypting messages before embedding, enhancing data confidentiality. The application of BeoF was validated through case studies, proving its efficacy in practical scenarios for both message embedding and extraction. Despite positive results, further optimization is suggested, including comparative studies with other steganographic and cryptographic methods to assess their relative advantages and limitations. This research affirms that BeoF is a robust and efficient solution for protecting sensitive information in the digital era.